2018
DOI: 10.1371/journal.pone.0206876
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of peripheral blood mononuclear cells miRNA expression and parasitic load in canine visceral leishmaniasis

Abstract: Visceral leishmaniasis (VL) in humans is a chronic and often fatal disease if left untreated. Dogs appear to be the main reservoir host for L. infantum infection, however, in many regions other canids such as jackals, foxes, wolves and other mammals, such as hares or black rats, have been implicated as wild reservoirs. Most dogs cannot form an effective immune response against this infection, and this could be modulated by small non-coding RNAs, called microRNAs, responsible for post-transcriptional control of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 58 publications
(61 reference statements)
0
32
0
Order By: Relevance
“…The initial steps of the inflammatory response occur during the phagocytosis of Leishmania and its establishment inside the phagolysosome and it is able to modulate the immune response by reducing the efficiency of inflammation and the development of an adaptive immune response [52][53][54][55]. Recent studies demonstrated that infections caused by L. amazonensis, L. infantum, L. major, and L. donovani can induce alteration in the miRNA profile from macrophages and dendritic cells of humans, murines, and dogs, thereby implicating the recognition and activation mechanisms of the immune response against parasites [56][57][58][59][60][61][62][63].…”
Section: Leishmania-host Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial steps of the inflammatory response occur during the phagocytosis of Leishmania and its establishment inside the phagolysosome and it is able to modulate the immune response by reducing the efficiency of inflammation and the development of an adaptive immune response [52][53][54][55]. Recent studies demonstrated that infections caused by L. amazonensis, L. infantum, L. major, and L. donovani can induce alteration in the miRNA profile from macrophages and dendritic cells of humans, murines, and dogs, thereby implicating the recognition and activation mechanisms of the immune response against parasites [56][57][58][59][60][61][62][63].…”
Section: Leishmania-host Interactionsmentioning
confidence: 99%
“…Furthermore, canine visceral leishmaniasis in symptomatic dogs who were naturally infected with L. infantum showed a differential modulation in the expression of miR-150, miR-451, miR-192, miR-194, and miR-371 in PBMCs, which can target genes to regulate the immune response and pathogenesis, such as NF-κB, TNF-α, CD80, and IFN-γ, which are important molecules related to resistance against the disease [62]. The L. infantum infection of human U937 and THP-1-derived macrophages upregulates miR-346, which decreases the mRNA level of genes initially associated with decreased MHC class I and II antigen presentation, TAP1, RFX1, and BCAP31.…”
Section: Leishmania-host Interactionsmentioning
confidence: 99%
“…Leishmania infection targets cellular miRNA repertoire and the differential miRNA expression is dependent on infecting species (37). A plethora of studies indicate miRNAs as key regulators of disease phenotype in Leishmania -infected cells (27, 30, 3234).…”
Section: Leishmania-induced Host Epigenetic Alterationsmentioning
confidence: 99%
“…Recently, small RNA sequencing identified differential enrichment of immune-regulatory microRNAs (miRNAs) in VL patient peripheral blood monocytes (PBMCs) and L. donovaniinfected THP-1 cells [17][18][19]. Muxel et al reported that Leismania amazoniensis infection alters TLR pathway mediators in infected macrophages via modulation of let-7e.…”
Section: Introductionmentioning
confidence: 99%